Structural configuration of a large-scale rotational earthslide at Syuchatar, Kathmandu, Nepal - Tamrakar, Naresh Kazi; Manandhar, Suman; Khanal, Subarna (Journal of Nepal Geological Society, 2007)
After a period of prolonged rain from 9 to 12 September 2005, a large rotational earthslide occurred on 16 September 2005 at Syuchatar in the Kathmandu valley. The horizontal fluvio-lacustrine strata constituting about 47 m high and 106 m long cliff as well as about 50 m wide upper flatland with paddy cultivation slipped towards the Manamati River and dammed it for about 8 hours. Later, its watercourse was restored by excavating a channel through the landslide debris. The earthslide also produced two minor scarps: the upper one with a rotation angle of 38º and the lower one with a rotation angle of 47º. A stereographic plot of poles to displaced coherent blocks forming the two minor scarps and dispersed fragmented blocks showed that the former had slid towards the northeast (N34ºE and N40ºE), and the latter had dispersed between the azimuths N13ºW and N60ºE. Though the in-situ infiltration test of the ground gave rather low rates, they were enough to produce a positive porewater pressure for triggering such a type of failure.